ANALISIS YURIDIS PERLAWANAN PELAKSANAAN ATAS EXECUTORIAL TITEL HAK TANGGUNGAN PADA PENGADILAN NEGERI - Rinaldi, Yosua (JURNAL ILMIAH LIVING LAW, 2016)
The Implementation Execution Mortagage Rights must be done to get the rest of the repayment of bank debtors. The mortgage becomes obstructed and delayed which will take tiume, effort and cost for the bank. Indefication of this research are: 1) what are the capacities executorial title associated with the determination of the Chairman of the District Court?; 2) How constraints execution executorial title by Deed of Encumbrances Encumbrance (APHT)?;Â  3) How does the concept of synergy with the implementation of civil law executorial title in execution of the security rights? The method used in the research is normative juridicial approach, the law conceived as norms, rules, principles or dogmas or jurispudence. The results of this research are: 1) Execution of Confiscation of secure inherent rights of dependents basically be required not longer, because the implementation of the confiscation of execution in the execution of a security interest to elimate the spirit of the mortgage; 2) Constraints execution executorial title by Deed of Encumbrances Encumbrance (APHT) is the existence of a lawsuit resistance from lender a security interest; 3) The enactment of Act Mortgage has made it clear that the execution parate not longer needed by the District Court.